Prediction of pre-exam state anxiety from ruminative disposition: The mediating role of impaired attentional disengagement from negative information. (April 2017) - Vălenaş, Sergiu P.; Szentágotai-Tătar, Aurora; Grafton, Ben; Notebaert, Lies; Miu, Andrei C.; MacLeod, Colin
Abstract: Rumination is a maladaptive form of repetitive thinking that enhances stress responses, and heightened disposition to engage in rumination may contribute to the onset and persistence of stress-related symptoms. However, the cognitive mechanisms through which ruminative disposition influences stress reactivity are not yet fully understood. This study investigated the hypothesis that the impact of ruminative disposition on stress reactivity is carried by an attentional bias reflecting impaired attentional disengagement from negative information. We examined the capacity of a measure of ruminative disposition to predict both attentional biases to negative exam-related information, and state anxiety, in students approaching a mid-term exam. As expected, ruminative disposition predicted state anxiety, over and above the level predicted by trait anxiety. Ruminative disposition also predicted biased attentional disengagement from, but not biased attentional engagement with, negative information. Importantly, biased attentional disengagement from negative information mediated the relation between ruminative disposition and state anxiety. These findings confirm that dispositional rumination is associated with difficulty disengaging attention from negative information, and suggest that this attentional bias may be one of the mechanisms through which ruminative disposition influences stress reactivity. Highlights: Effects of rumination on attentional bias and pre-exam state anxiety were assessed. Rumination predicted pre-exam state anxiety over and above trait anxiety. Rumination predicted attentional disengagement, but not attentional engagement bias. Disengagement bias was a mediator between rumination and state anxiety.